Double‐stranded RNAs targeting inhibitor of apoptosis gene show no significant cross‐species activity. Issue 4 (29th April 2020) - Chereddy, Shankar C. R. R.; Gurusamy, Dhandapani; Howell, Jeffrey L.; Palli, Subba R.
Abstract: RNA interference (RNAi) has become an integral part of mainstream research due to its versatility and ease of use. However, the potential nontarget effects associated with double‐stranded RNAs (dsRNA) are poorly understood. To explore this, we used dsRNAs targeting the inhibitor of apoptosis ( iap ) gene from nine insect species and assayed their possible nontarget effects. For each assay, we used a control (dsRNA targeting the gene coding for green fluorescent protein, GFP) and a species‐specific dsRNA targeting nine iap genes in insect species to evaluate target gene knockdown efficiency, apoptosis phenotype in cells and mortality in insects. Our results revealed that dsIAP efficiently knocks down iap gene expression and induces apoptosis phenotype and mortality in target insect species. In contrast, no significant knockdown of the iap gene expression, apoptosis phenotypes, or mortality were detected in cell lines developed from nontarget insects or nontarget insects treated with dsIAPs. Interestingly, even among closely related insects such as stink bugs, Nezara viridula, Halyomorpha halys, and Murgantia histrionica, with substantial sequence similarity among iap genes from these insects, no significant nontarget effects of dsIAP were observed under the conditions tested. These data demonstrate no significant nontarget effects for dsIAPs and suggest that the threat of nontarget effects of RNAi technology may not be substantial. Abstract : Analysis of domains present in the coding sequences of iap genes from nine insect species. The coding sequences of iap genes from Spodoptera frugiperda ( Sf ), Leptinotarsa decemlineata ( Ld ), Tribolium castaneum ( Tc ), Anoplophora glabripennis (Ag ), Lasioderma serricorne ( Ls ), Aedes aegypti ( Aa ), Halyomorpha halys ( Hh ), Murgantia histrionica ( Mh ), and Nezara viridula ( Nv ) were selected and the presence of conserved domains were analyzed using the NCBI Conserved domain search tool. The boxes indicate the location of conserved domains and the red arrows indicate the position of the dsRNA target sequences. BIR, baculoviral IAP repeat Research Highlights: Double‐stranded RNA targeting inhibitor of apoptosis (dsIAP) knocks down the target gene and induces apoptosis and mortality in target insects. No knockdown of the iap gene, apoptosis, or mortality were detected in nontarget insects or cell lines developed from them treated with dsIAP.